Interaction between attentional allocation, social connectedness, and problem behaviors: a brief review and pilot data - Seonmi Yun; Suk Won Han (Environment and Social Psychology, 2025)
The present study investigated how a core, elementary cognitive process, attentional orienting is related to social connectedness and problem behaviors. Prior research links social cognition difficulties in autism and other attention-related conditions to deficits in visual attention. We reviewed this evidence and proposed a plausible experimental paradigm to clarify the interaction between attention and social function. We also present a pilot data supporting our proposition. Specifically, our study involved 30 participants who completed a modified version of attentional cuing task, the Adult Self-Report, and the Sociotype Questionnaire (SOCQ) to evaluate social functioning and attentional function. A mixed-model ANOVA showed a significant interaction between the magnitude of the cuing effect and ASR scores, suggesting reduced attentional benefits with higher levels of self-reported maladaptive behaviors. Further, we observed a significant negative correlation between ASR and SOCQ scores, indicating that individuals with higher problem behavior scores reported greater social difficulties. These findings contribute to the growing evidence that visual attention capabilities are linked to social adaptability, suggesting that visual attentional mechanisms may play a role in facilitating social interactions in adults. This study opens avenues for exploring visual attention’s influence on social competency beyond clinical populations, providing insights into the visual-cognitive processes underpinning social functioning in typical development.